Identification of potential plasma protein markers for gestational diabetes mellitus - Sangaran, Puspha Gandi (2012)
Gestational Diabetes Mellitus (GDM) is defined as glucose intolerance that is detected during pregnancy. It is caused by the decreased sensitivity of insulin with increasing gestation week. Identifying this group of women is important in not only preventing perinatal morbidity but also improving long term outcomes for the mothers and their children. The usual approach in diagnosing GDM is to screen GDM patients during the second trimester of gestation through an oral glucose tolerance test (OGTT). There is potential harm and high costs may be involved in screening, especially given the high false-positive rate. However, there is a need to diagnose GDM as early as possible to minimize the undesirable effects in the development of the fetus. In this exploratory study, two dimensional gel electrophoresis (2DGE) and Liquid Chromatography Mass Spectrometry (LC/MS/MS) were used in the quest for new potential biomarkers for the disease. The purpose of this study was to identify a set of potential protein markers which are differentially expressed during the first, second or third trimester of pregnancy. Once identified and validated, the candidate biomarkers for GDM could provide opportunities for rapid and low-cost screening. For this study, five millilitres of fresh blood was drawn for each trimester of pregnancy from five normal pregnant women and five GDM patients at Hospital Kuala Lumpur and Klinik Kesihatan Seri Kembangan. The plasma samples were used for 2DGE, where proteins are separated first by characteristic isoelectric point using isoelectrofocusing, and then by protein molecular weight, using sodium dodecylsulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The 2D gels were stained using Colloidal Coomassie Blue stain and scanned by using a high resolution imager. The images were quantitatively analyzed using Nonlinear Progenesis SameSpots Software to identify protein spots that demonstrate significant differences in expression between the GDM samples and with normal pregnant samples. Spots demonstrating significant differences were manually picked using sterile procedure and identified by LC/MS/MS analysis through a service from the Proteomics Centre at Medical University of South Carolina. In this study, 11 distinct proteins were identified which were expressed differentially in the plasma of normal pregnant women and plasma from GDM patients. The proteins were Alpha-1-Antitrypsin, Albumin, Antithrombin III, Fibrinogen, Apolipoprotein A1, Apolipoprotein E, Alpha 1B-Glycoprotein, Complement Factors, Angiotensinogen, Transferrin, and Vitamin D binding protein. Among these proteins, Antithrombin III, Apolipoprotein E and Vitamin D binding protein could be candidates to screen the GDM patients. Further studies are recommended to validate these candidate biomarkers by using ELISA and western blotting.